THE THEORY OF PRIMORDIALITY: A TRANSDISCIPLINARY APPROACH TO PARADIGMS IN THE HISTORY OF SCIENCE - Neves, Afonso Carlos (RECIMA21 - Revista Científica Multidisciplinar - ISSN 2675-6218, 2022)
This is a debate about methodology in the history of science and its correlations with society and culture. Since the work of Thomas Kuhn about paradigms, the vision of historical succession of events in science has changed. Concurrently, Robert Merton incremented his sociological study of science, where he proposed what he named as “multiple in science”, to explain the concomitancy of similar discoveries at the same time. Furthermore, before the main event in scientific discoveries and inventions, there are precedent studies or scientific practices which could explain that discovery or invention more as a process than as a single event. Therefore, we propose the Theory of Primordiality to embrace the several primordial events that are correlated with a considered discovery or invention in a historical process even in a long period. That historical process has links among several occurrences surrounding the same aim of the main paradigmatic event, but without substituting it. For this proposal, we studied concepts in methods of history research that tried to reach correlations among processes surrounding scientific discoveries and inventions, including notions of zeitgeist and creativity in science.